Reverse degradation of nickel graphene junction by hydrogen annealing - Zhenjun Zhang; Fan Yang; Pratik Agnihotri; Ji Ung Lee; J. R. Lloyd (AIP Advances, 2016)
Metal contacts are fundamental building components for graphene based electronic devices and their properties are greatly influenced by interface quality during device fabrication, leading to resistance variation. Here we show that nickel graphene junction degrades after air exposure, due to interfacial oxidation, thus creating a tunneling barrier. Most importantly, we demonstrate that hydrogen annealing at moderate temperature (300 0C) is an effective technique to reverse the degradation.